Handbook of the Life Course
XX, 728 p.
Keywords: This comprehensive handbook provides an overview of key theoretical perspectives, concepts, and methodological approaches that, while applied to diverse phenomena, are united in their general approach to the study of lives across age phases. In surveying the wide terrain of life course studies with dual emphases on theory and empirical research, this important reference work presents probative concepts and methods and identifies promising avenues for future research. Included are sections on history and cross-national variability, normative structuring, movement through the life course, transitions in the life course, turning points, connections between life phases, methodology, and the future of the life course. A major reference work and a seminal text, it is essential reading for social scientists studying phases within the life course, social psychologists in sociology and psychology, demographers and academics in the field of the life course as well as students in thesedisciplines.